The Dandelion Principle Redesigning Work for the Innovation Economy - Sonne, Thorkil; Austin, Robert (MIT Sloan Management Review, 2014)
In May 2013, software giant SAP announced plans to hire hundreds of people diagnosed with autism, with a target of having people with autism represent 1% of the company's work force by 2020. The Merriam-Webster dictionary defines autism as a developmental disorder associated with "impairment of the ability to communicate with others" and "preoccupation with repetitive activities of restricted focus." Companies don't typically seek out these characteristics in new hires. But SAP took a different perspective. "We share a common belief that innovation comes from the 'edges,'" one SAP executive stated in the company's press release. "Only by employing people who think differently and spark innovation will SAP be prepared to handle the challenges of the 21st century." More specifically, the company had discovered that some people with autism have abilities that are extremely well-suited to performing some vital information technology tasks. SAP's move embodies an emerging management principle -- the authors Robert D. Austin and Thorkil Sonne call it "the dandelion principle" -- and offers an alternative way of thinking about human resources management. In some ways, the "dandelion principle" turns some of the basic tenets about how to recruit and manage people inside out. The authors use the dandelion as metaphor because, they note, dandelions are actually nutritious -- but are seen as weeds in the context of a green lawn that demands uniformity. The industrial economy, the authors argue, required uniformity in operations. In the industrial economy, companies could often win by operating more efficiently than rivals. Today, that's no longer enough. Faced with lower-cost competition from developing countries, established companies also need to innovate, to offer products that are better than what's available from competitors. But innovation, the authors observe, calls for organizational capabilities different than efficiency. Efficiency requires getting people and machines to mesh more smoothly; the emphasis is on parts fitting in and reducing variation around averages. Innovation, by contrast, involves finding new and better ideas and using new processes. Managing innovation is less about averages and more about understanding outliers. The emphasis is on increasing interesting variation, then identifying value in some of the variants. In an innovation-oriented economy, the authors contend, companies may benefit from accommodating employees wit...